EFEKTIVITAS BIOATRAKTAN DARI BAHAN ALAMI TERHADAP RAYAP TANAH (Coptotermes curvignathus Holmgren) - Permana, Rizka Diah; Husni, Harnani (JURNAL HUTAN LESTARI, 2017)
The purpose of this research is to know the effectiveness of the mixture of eucalyptus leaf extract 0,01%, degraded pine wood, official waste paper, and cardboard waste as bioattractant against subterranean termites Coptotermes curvignathus and to know the effectiveness composition of the bait as a bioattractant against subterranean termites Coptotermes curvignathus. The examination was done with 2 methods, no choice test and multiple choice test. The observation including weight loss of test sample and termite mortality. Results showed that type of bait has significant different to weight loss in both no choice test and multiple choice. The highest value of weight loss in no choice test was noted at the composition of degraded pine wood + official waste paper + cardboard waste + eucalyptus leaf extract 0,01%, with a value of 10,7685% and the lowest value of weight loss was noted at the composition of official waste paper, with a value of 1,3642%. The highest value of weight loss in multiple choice test was recorded at composition of degraded pine wood + official waste paper + cardboard waste + eucalyptus leaf extract 0,01%, with value of 9,3863% and the lowest value ofÂ  weight loss was at with composition of official waste paper + cardboard waste, with value of 0,8783%. Types of bait are also significantly different to termite mortality. The highest value of termite mortality was noted at sample with composition of degraded pine wood + official waste paper + cardboard waste + eucalyptus leaf extract 0,01%, with value of 51,3333% and the lowest termite mortality was at sample with composition of degraded pine wood + official waste paper + cardboard waste, with value of 22%. Bait formulation of degraded pine wood + official waste paper + cardboard waste + eucalyptus leaf extract 0,01% effective as bioattractant against Coptotermes curvignathus Holmgren.Keywords: Baiting method, Bioattractant, Coptotermes curvignathus, Maleuca leucadendra, Pinus merkusii.